Readability and Quality of Online Health Information Regarding Parathyroidectomy - Jim Byrne MCh; Samuel Keogh MB BCh BAO; Carolyn Cullinane MCh, MRCS; Zeeshan Razzaq MBBS, FRCSI; Henry Paul Redmond PhD, FRCSI (OTO Open, 2022)
Objective Assessment of the readability and quality of online health information regarding parathyroidectomy. Study Design Cross-sectional analysis. Setting Websites providing patient-oriented health information regarding parathyroidectomy obtained via the Google search engine. Methods The top 75 Google search results for “parathyroidectomy,”“parathyroid surgery,” and “parathyroid gland removal” were reviewed. Websites were categorized by website type and country of origin. Readability was assessed by Flesch-Kincaid Grade Level and Simple Measure of Gobbledygook. Website quality was assessed per JAMA benchmark criteria and the DISCERN instrument. Results A total of 74 unique websites were evaluated. The mean readability of the assessed websites exceeded the recommended sixth-grade reading level on the Flesch-Kincaid Grade Level and Simple Measure of Gobbledygook ( P < .001). Readability did not vary significantly by website type. Websites originating from the United Kingdom were significantly more readable than those from the United States. The majority of assessed websites were of poor quality (n = 42, 56.8%) on assessment based on the DISCERN instrument. Quality varied significantly by website category on the JAMA benchmark criteria ( P < .001) and DISCERN score ( P = .049) with commercial websites receiving the highest scores. DISCERN score also varied significantly by country of origin ( P = .036) with UK sites receiving highest mean DISCERN scores. Conclusion Online health information regarding parathyroidectomy is largely of poor quality and is poorly readable for many patients. Institutions utilizing well-defined guidelines for development of patient educational resources may provide online health information of greater quality and readability.